Selecting Content Analysis Approach in Social Networking Sites: What’s the Best for Cyberbullying Studies? - Budianto Hamuddin; Fathu Rahman; Abidin Pammu; Yusring Sanusi Baso; Tatum Derin (Universitas Jambi, Indonesia, 2020)
Insight into students’ behaviour and interaction is essential when it comes to improving the development and implementation of educational policies. Content analysis is a staple method to study online communication. However, there seems to be no clear reference for researchers to decide which approach is suitable to address a particular purpose. So, this study aims to recommend the most suitable content analysis approach for SNS research. This study extracted relevant studies from open-access databases and analysed the full-texts with NVivo 12. From a raw data collection of 120 texts, this study identified 19 approaches. This study recommends four approaches which are ideal to study cyberbullying among students in the higher education context, specifically on the types, styles, motives, and solutions of cyberbullying. First is Neuendorf’s descriptive content analysis approach to study about the types. Second is Hijmans’ rhetorical content analysis to study the styles. Third is Hsieh and Shannon’s directed content analysis approach to study the motives. Fourth is Miles and Huberman’s collaborative social content analysis to study the solutions. These four approaches have different focuses that seem to be the perfect match to study different aspects of online interaction on SNS, particularly in the context of cyberbullying.